2013
DOI: 10.5254/rct.13.87969
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Chemical Structure and Mechanical Property Levels During Thermo-Oxidative Aging of NBR

Abstract: The accelerated thermo-oxidative aging of acrylonitrile–butadiene rubber (NBR) was studied at elevated temperatures. The chemical structure characterized by attenuated total reflectance–Fourier transform infrared spectroscopy (ATR-FTIR) and pyrolysis gas chromatography–mass spectroscopy (PGC-MS) showed the loss of low-molecular-weight additives, such as antioxidants and paraffin, and the formation of carbonyl groups and unsaturated double bonds. The cross-linking degree characterized by NMR and a swelling test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 1 publication
2
64
0
Order By: Relevance
“…For the samples exposed to air, the peak at 1733 cm −1 first increased and then decreased with increasing aging time, implying the formation and consumption of carboxyl groups. However, when the compressed samples were immersed in the hydraulic oil, the intensity of the peak at 1733 and 1532 cm −1 decreased substantially, possibly due to the extraction of additives (such as stearic acid and plasticizer) by the oil . It can be concluded that carboxyl groups and hydroxyl groups were formed on the compressed samples exposed to air during the aging process, and that hydroxyl groups were produced in the compressed samples exposed to oil.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For the samples exposed to air, the peak at 1733 cm −1 first increased and then decreased with increasing aging time, implying the formation and consumption of carboxyl groups. However, when the compressed samples were immersed in the hydraulic oil, the intensity of the peak at 1733 and 1532 cm −1 decreased substantially, possibly due to the extraction of additives (such as stearic acid and plasticizer) by the oil . It can be concluded that carboxyl groups and hydroxyl groups were formed on the compressed samples exposed to air during the aging process, and that hydroxyl groups were produced in the compressed samples exposed to oil.…”
Section: Resultsmentioning
confidence: 96%
“…Hydrogenated nitrile butadiene rubber (HNBR) O‐rings are well known for their resistance to thermal oxidation, chemical mediums and mechanical stress, and are usually applied in hydraulic systems to inhibit leaks of liquids or gases . However, under actual service conditions, the O‐rings are often subjected to harsh environments, such as mechanical stress (often compressive stress), high temperatures (up to 150 °C) and both gaseous (air) and liquid (hydraulic oil) environments, leading to substantial degradation of the chemical structure and mechanical properties of the seals . The degradation of these seals causes sealing failures in the hydraulic system, resulting in leakages of air or hydraulic oil.…”
Section: Introductionmentioning
confidence: 99%
“…2, favors the hypothesis of oxidation-induced crosslinking. Evidences of such reaction have been shown in our previous work [6]. Of course, oxidative chain scission also took place simultaneously, in favor of increasing chain mobility and releasing the stress.…”
Section: Effect Of Atmospherementioning
confidence: 82%
“…Its aging resistance is of great importance and thus concerned because of the unsaturated backbone of the butadiene part [22]. During thermal aging, mainly three changes occurred successively: (1) of macromolecular chains [23].…”
Section: Introductionmentioning
confidence: 99%